Implementasi Manajemen Strategi dalam Lembaga Pendidikan - Faujiah, Syifa; Syaifudin, Muhammad; Andriani, Tuti (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The purpose of making this paper is to find out about management strategies, Islamic education management strategies, and the factors that influence Islamic education management strategies. Through strategic management, future opportunities can be expanded and realized risks can be minimized. Strategic management can only be achieved if all parties with a direct interest in the school, such as school administrators, parents, lecturers and staff, are involved. Strategic management is the implementation of planning, monitoring, analysis and evaluation that is carried out on an ongoing basis from all the needs required by the organization in an effort to achieve its goals. Changes that occur quickly and spontaneously in the organizational environment will require an organization that is capable of continuously evaluating strategies. The implementation of strategic management helps the organization to know the current condition of the organization, then formulates a strategy, deploys it and analyzes the effectiveness of the implemented management strategy. This study aims to determine the implementation of strategic management in educational institutions.